PENGEMBANGAN MOTIF BATIK DAUN PUCUK UBI DI DESA EMPELU, KECAMATAN TANAH SEPENGGAL, KABUPATEN BUNGO - Attia Martina; Eliya Pebriyeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a development study of the Batik Daun Pucuk Ubi motif in Empelu Village, Tanah Sepenggal Sub-district, Bungo Regency, motivated by the issue of limited public knowledge and awareness in developing existing batik motifs. The aim of this research is to determine the level of development, validity, and practicality of the motif. This study applies the Research and Development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate), with qualitative and quantitative descriptive data analysis techniques. The trial subjects in this study were 10 members of the Empelu Village PKK community. Validation results from experts showed that the motif design scored between 84%–93.33%, categorized as valid to highly valid, especially in terms of uniqueness, aesthetics, and cultural relevance, while color validation reached 86.67%, indicating that the color combinations were considered attractive and innovative. The practicality test by the PKK members yielded a score of 96.2%, indicating that the motif is highly suitable for use in community training and production. These findings suggest that the Batik Daun Pucuk Ubi motif has the potential to become a local visual identity and a valuable cultural product.